2009
DOI: 10.1007/s12603-009-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining nutrition in aged care residents with a train-the-trainer intervention and nutrition coordinator

Abstract: The results of the study encourage the implementation of a Nutrition Coordinator program to maintain nutritional status of aged care residents. Nevertheless, malnutrition rates continue to be unacceptably high. In a rapidly aging society, the aged care sector needs to confront malnutrition and provide better resources for staff to take measures against this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The original study identified the malnutrition prevalence of residents (Gaskill et al. , 2008) and the impact of implementing a train‐the‐trainer nutrition program versus usual care on the nutritional status of residents after 6 months (Gaskill et al. , 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The original study identified the malnutrition prevalence of residents (Gaskill et al. , 2008) and the impact of implementing a train‐the‐trainer nutrition program versus usual care on the nutritional status of residents after 6 months (Gaskill et al. , 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The education of the nutrition coordinator includes three whole-day courses plus train-the-trainer sessions with other staff members (based on [13]) and local study circles in-between (based on [17]). These nutrition coordinators will be active in both the control and the intervention group.…”
Section: Methodsmentioning
confidence: 99%
“…One of these actually documented a positive effect nutritional and functional status of a multidisciplinary intervention consisting of energy- and protein dense home-made oral supplements, exercise and oral care [12]. While the other found that a multidisciplinary intervention consisting of education of nutrition coordinators including train-the-trainer sessions were able to maintain nutritional status [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, staff education, regular monitoring for nutritional risk and weight, with prompt and individualised triage for malnourished residents is crucial in the management of malnutrition (93)(94)(95). In addition, the training and appointment of a staff member as a nutrition coordinator or champion has also demonstrated positive results in managing malnutrition in RAC (96)…”
Section: Nutritional Management Of Malnutrition In Racmentioning
confidence: 99%